Human Papillomavirus 16 E2 as an Apoptosis-Inducing Protein for Cancer Treatment: A Systematic Review - Dinah Farhanah Jamal; Quratul Ain Rozaimee; Nadila Haryani Osman; Atikah Mohd Sukor; Marjanu Hikmah Elias; Nor Aripin Shamaan; Srijit Das; Nazefah Abdul Hamid (MDPI, 2024)
Indexed by WOS/SCOPUS/ERA